Heat transfer in rectangular microchannels heat sink using nanofluids - Mohammed H.A.; Gunnasegaran P.; Shuaib N.H. (2023)
The effect of using nanofluids on heat transfer and fluid flow characteristics in rectangular shaped microchannel heat sink (MCHS) is numerically investigated for Reynolds number range of 100-1000. In this study, the MCHS performance using alumina-water (Al2O3-H2O) nanofluid with volume fraction ranged from 1% to 5% was used as a coolant is examined. The three-dimensional steady, laminar flow and heat transfer governing equations are solved using finite volume method. The MCHS performance is evaluated in terms of temperature profile, heat transfer coefficient, pressure drop, friction factor, wall shear stress and thermal resistance. The results reveal that when the volume fraction of nanoparticles is increased under the extreme heat flux, both the heat transfer coefficient and wall shear stress are increased while the thermal resistance of the MCHS is decreased. However, nanofluid with volume fraction of 5% could not be able to enhance the heat transfer or performing almost the same result as pure water. Therefore, the presence of nanoparticles could enhance the cooling of MCHS under the extreme heat flux conditions with the optimum value of nanoparticles. Only a slight increase in the pressure drop across the MCHS is found compared with the pure water-cooled MCHS. 2010 Elsevier Ltd.